Cellular automata: Towards possible applications in urban design education and practice | Autômatos celulares: visando possíveis aplicações no ensino e na prática do urbanismo - Oliveira e Sousa, Marcela Noronha Pinto de; Caffarena Celani, Maria Gabriela (Oculum Ensaios, 2019)
This article investigates how Cellular Automata have been applied to the design process in the fields of architectural and urban design. It begins by systematically mapping published applications of Cellular Automata in the design process in order to outline the state of the art. The methods employed in the reviewed papers are analyzed and contrasted in order to develop a conceptual framework to guide future applications of Cellular Automata as a tool in the urban design process in academic environments, aiming at future applications in actual practice.